Cover Picture: Physical Properties of Superbulky Lanthanide Metallocenes: Synthesis and Extraordinary Luminescence of [EuII(CpBIG)2] (CpBIG=(4‐nBu‐C6H4)5‐Cyclopentadienyl) (Chem. Eur. J. 37/2013). Issue 37 (2nd September 2013) - Harder, Sjoerd; Naglav, Dominik; Ruspic, Christian; Wickleder, Claudia; Adlung, Matthias; Hermes, Wilfried; Eul, Matthias; Pöttgen, Rainer; Rego, Daniel B.; Poineau, Frederic; Czerwinski, Kenneth R.; Herber, Rolfe H.; et al.
<x xml:space="preserve">Abstract</x> High luminescence is observed for an Eu2+ ion sandwiched between two bulky cyclopentadienyl ligands, as described by S. Harder et al. in their Full Paper on page 12272 ff. In contrast to [Eu(Cp*)2] (Cp* = pentamethylcyclopentadienyl), which hardly shows luminescence, a quantum yield of 45% is found for the europocene [Eu(CpBIG)2] (CpBIG=(4‐nBu‐C6H4)5‐cyclopentadienyl). Magnetic susceptibility measurements, and Mössbauer as well as EXAFS spectroscopy rule out possible oxidation‐state ambiguities for the lanthanide(II) metallocenes of Sm, Eu, and Yb.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>